Odpowiedzi

Najlepsza Odpowiedź!
2010-01-11T21:43:58+01:00
A) A=(-5;0) B=(0;-2) C=(2;2)
|AB|^2=(0+5)^2+(-2-0)^2=25+4=29
|BC|^2=(2-0)^2+(2+2)^2=4+16=20
|AC|^2=(2+5)^2+(2-0)^2=49+4=53

|AB|^2+|BC|^2<|AC|^2
Trójkąt nie jest prostokątny

b) A=(4;-1) B=(1;5) C=(-4;3)
|AB|^2=(1-4)^2+(5+1)^2=9+36=45
|BC|^2=(-4-1)^2+(3-1)^2=25+4=29
|AC|^2=(-4-4)^2+(3+1)^2=64+16=80

|AB|^2+|BC|^2<|AC|^2
Trójkąt nie jest prostokątny

C) A=(-3;-1) B=(6;-4) C=(7;-1)
AB|^2=(6+3)^2+(-4+1)^2=81+9=90
|BC|^2=(7-6)^2+(-1+4)^2=1+9=10
|AC|^2=(7+3)^2+(-1+1)^2=100+0=100

|AB|^2+|BC|^2=|AC|^2
Trójkąt jest prostokątny